Immune modulatory effects of progesterone on oxLDL-induced trained immunity in monocytes. Issue 2 (17th January 2022) - Groh, Laszlo A; Verel, Dagmar E; van der Heijden, Charlotte D C C; Matzaraki, Vasiliki; Moorlag, Simone J C F M; de Bree, L Charlotte; Koeken, Valerie A C M; Mourits, Vera P; Keating, Samuel T; van Puffelen, Jelmer H; Joosten, Leo A B; Netea, Mihai G; et al.
Abstract: Atherosclerotic cardiovascular diseases (CVD) are among the leading causes of death in the world. Monocyte-derived macrophages are key players in the pathophysiology of atherosclerosis. Innate immune memory following exposure of monocytes to atherogenic compounds, such as oxidized low-density lipoproteins (oxLDL), termed trained immunity, can contribute to atherogenesis. The current study aimed to elucidate intracellular mechanisms of oxLDL-induced trained immunity. Using untargeted intracellular metabolomics in isolated human primary monocytes, we show that oxLDL-induced trained immunity results in alterations in the balance of intracellular steroid hormones in monocytes. This was reflected by a decrease in extracellular progesterone concentrations following LPS stimulation. To understand the potential effects of steroid hormones on trained immunity, monocytes were costimulated with oxLDL and the steroid hormones progesterone, hydrocortisone, dexamethasone, β-estradiol, and dihydrotestosterone. Progesterone showed a unique ability to attenuate the enhanced TNFα and IL-6 production following oxLDL-induced trained immunity. Single nucleotide polymorphisms in the nuclear glucocorticoid, progesterone, and mineralocorticoid receptor were shown to correlate with ex vivo oxLDL-induced trained immunity in 243 healthy volunteers. Pharmacologic inhibition experiments revealed that progesterone exerts the suppression of TNFα in trained immunity via the nuclear glucocorticoid and mineralocorticoid receptors. Our data show that progesterone has a unique ability to suppress oxLDL-induced trained immunity. We hypothesize that this effect might contribute to the lower incidence of CVD in premenopausal women. Graphical Abstract: Cytokine production by oxLDL-induced trained immunity is inhibited by the steroid hormone progesterone.